Relative age effect and Yo-Yo IR1 in youth soccer - Deprez, D.; Vaeyens, R.; Coutts, A. J.; Lenoir, M.; Philippaerts, R. (International Journal of Sports Medicine, 2012)
The aims of the study were to investigate the presence of a relative age effect and the influence of birth quarter on anthropometric characteristics, an estimation of biological maturity and performance in the Yo-Yo Intermittent Recovery Test level 1 in 606 elite, Flemish youth soccer players. The sample was divided into 5 chronological age groups (U10-U19), each subdivided into 4 birth quarters. Players had their APHV estimated and height, weight and Yo-Yo IR1 performance were assessed. Differences between quarters were investigated using uni- and multivariate analyses. Overall, significantly (P<0.001) more players were born in the first quarter (37.6%) compared to the last (13.2%). Further, no significant differences in anthropometric variables and Yo-Yo IR1 performance were found between the 4 birth quarters. However, there was a trend for players born in the first quarter being taller and heavier than players born in the fourth quarter. Players born in the last quarter tended to experience their peak in growth earlier, this may have enabled them to compete physically with their relatively older peers. Our results indicated selection procedures which are focused on the formation of strong physical and physiological homogeneous groups. Relative age and individual biological maturation should be considered when selecting adolescent soccer players.